Economic Sustainability Through Agritourism in Rural Communities: The Case of Native Chicken Beauty Contest in Isabela, Philippines - Noemi C. Liangco; Sutthikarn Khong-Khai; Winitra Leelapattana; Weerapon Thongma (Buletin Peternakan, 2023)
Agritourism is a promising industry in the Philippines. It is one among the backbones of Philippine economy. This study assessed the impact of the native chicken beauty contest as an agritourism initiatives in Isabela, Philippines based on the perceptions of 639 farmers and stakeholders. The participants are coming from different municipalities of the province. Data were gathered through an adapted survey. Findings revealed that the respondents have a positive perception on the impact of the initiatives in the aspect of economy. They believe that the initiative improves their financial status, and that they received strategic and financial support from the government through their political leaders. On the other hand, the participants’ concern was about peoples’ participations to the development and implementation of the initiatives, proper development of community image for branding towards international recognition. Hence, a policy on inter-agency and inter-cultural monitoring board is highly recommended.